Plasma-Derived Extracellular Vesicles Reveal Galectin-3 Binding Protein as Potential Biomarker for Early Detection of Glioma - Rana, Rashmi; Chauhan, Kirti; Gautam, Poonam; Kulkarni, Mahesh; Banarjee, Reema; Chugh, Parul; Chhabra, Satnam Singh; Acharya, Rajesh; Kalra, Samir Kumar; Gupta, Anshul; Jain, Sunila; Ganguly, Nirmal Kumar (Frontiers in Oncology, 2021)
Gliomas are the most common type of the malignant brain tumor, which arise from glial cells. They make up about 40% of all primary brain tumors and around 70% of all primary malignant brain tumors. They can occur anywhere in the central nervous system (CNS), and have a poor prognosis. The average survival of glioma patients is approximately 6-15 months with poor aspects of life. In this edge, identification of proteins secreted by cancer cells is of special interest because it may provide a better understanding of tumor progression and provide early diagnosis of the diseases. Extracellular vesicles (EVs) were isolated from pooled plasma of healthy controls (n=03) and patients with different grades of glioma (Grade I or II or III, n=03 each). Nanoparticle tracking analysis, western blot and flow cytometery were performed to determine the size, morphology, the concentration of glioma-derived vesicles and EV marker, CD63. Further, iTRAQ based LC-MS/MS analysis of EV protein was performed to determine the differential protein abundance in extracellular vesicles across different glioma grades. We further verified galactin-3-binding protein (LGALS3BP) by ELISA in individual blood plasma and plasma-derived vesicles from control and glioma patients (n=40 each). Analysis by Max Quant identified 123 proteins from the pooled patient exosomes, out of which 34, 21 and 14 proteins were found to be differentially abundant by more than 1.3-fold in the different grades of glioma grade I-pilocytic astrocytoma, grade II- diffuse astrocytoma, grade III- anaplastic astrocytoma respectively in comparison with the control samples. A total of 7 proteins namely CRP, SAA2, SERPINA3, SAA1, C4A, LV211 and KV112, showed differential abundance in all the three grades. LGALS3BP was seen to be up-regulated across the different grades and ELISA analysis from individual blood plasma and plasma derived extracellular vesicles confirmed the increased expression of LGALS3BP in glioma patients (p<0.001). The present study provides LGALS3BP as a potential biomarker for early detection of glioma and improve survival outcome of the patient. The present study further provides the information of progression and monitoring the tumor grades (grade 1, grade II, grade III).